Should we keep on? Looking into pharmacogenomics of ADHD in adulthood from a different perspective. (July 2014) - Rovaris, Diego L; Mota, Nina R; da Silva, Bruna Santos; Girardi, Pricila; Victor, Marcelo M; Grevet, Eugenio H; Bau, Claiton HD; Contini, Verônica
A considerable proportion of adults with attention-deficit/hyperactivity disorder (ADHD) do not respond to the treatment with methylphenidate. This scenario could be due to inherited interindividual differences that may alter pharmacologic treatment response. In this sense, in 2012 we conducted a systematic search on PUBMED-indexed literature for articles containing information about pharmacogenomics of ADHD in adults. Five studies were found on methylphenidate pharmacogenomics and the only significant association was reported by one particular study. However, this single association with the SLC6A3 gene was not replicated in two subsequent reports. In the present review, although we could not find additional pharmacogenomics studies, we discuss these up-to-date findings and suggest new approaches for this field. Additionally, using systeomic-oriented databases, we provide a broad picture of new possible candidate genes as well as potential gene–gene interactions to be investigated in pharmacogenomics of persistent ADHD.